2005
DOI: 10.1016/j.cognition.2004.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Age of acquisition effects in picture naming: evidence for a lexical-semantic competition hypothesis

Abstract: In many tasks the effects of frequency and age of acquisition (AoA) on reaction latencies are similar in size. However, in picture naming the AoA-effect is often significantly larger than expected on the basis of the frequency-effect. Previous explanations of this frequency-independent AoA-effect have attributed it to the organisation of the semantic system or to the way phonological word forms are stored in the mental lexicon. Using a semantic blocking paradigm, we show that semantic context effects on naming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
144
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(160 citation statements)
references
References 23 publications
12
144
1
3
Order By: Relevance
“…The modulation of amplitudes observed between 220 and 250 ms, falls within the time-window estimated for lexical-semantic encoding process (Indefrey and Level, 2004); it therefore seems to support the hypothesis of a lexical-semantic locus of AoA effect (e.g., Belke et al, 2005;Johnston & Barry, 2005). However, further differences in amplitudes between early-and late-acquired words also appeared in a timewindow corresponding to lexical-phonological encoding (330-350 ms after picture onset and around 280 ms before RT).…”
Section: Aoa Effectsupporting
confidence: 75%
See 2 more Smart Citations
“…The modulation of amplitudes observed between 220 and 250 ms, falls within the time-window estimated for lexical-semantic encoding process (Indefrey and Level, 2004); it therefore seems to support the hypothesis of a lexical-semantic locus of AoA effect (e.g., Belke et al, 2005;Johnston & Barry, 2005). However, further differences in amplitudes between early-and late-acquired words also appeared in a timewindow corresponding to lexical-phonological encoding (330-350 ms after picture onset and around 280 ms before RT).…”
Section: Aoa Effectsupporting
confidence: 75%
“…This 6 hypothesis is based on the fact that AoA effects were observed neither in lexical-semantic tasks (Chalard & Bonin, 2006;Morrison et al, 1992) nor in delayed production tasks (Morrison & Ellis, 1995), therefore excluding lexical-semantic encoding levels or motor processes. However, AoA effects have been recently reported with semantic tasks (Belke, Brysbaert, Meyer, & Ghyselinck, 2005;Johnson & Barry, 2005), supporting the alternative hypothesis of a lexical-semantic locus of AoA effects.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…He reported that the effect of AoA was greater in naming pictures than words, and the effect of semantic context in naming early-acquired words was more substantial than in lateacquired ones. This effect was not found in word reading, since word reading does not involve Lemma stage (7). In addition, Morrison investigated the hypothesis of the AoA effect semantic locus by picture categorization task and reported no effect of AoA (10).…”
Section: Introductionmentioning
confidence: 98%
“…Some studies reported that Early Acquired Words (EAW) were named faster than Late Acquired Words (LAW), and the words acquired earlier in life are more reversible after a brain injury (5,6). In many tasks the effects of frequency and AoA on reaction latencies are equal, but in picture naming the effect of AoA is greater than frequency (7). As far as the locus of AoA effects in picture naming is concerned, the phonological retrieval stage is the one proposed most frequently.…”
Section: Introductionmentioning
confidence: 99%